Viral gastroenteritis - Desselberger, Ulrich (Medicine (Abingdon), 2017)
This article reviews the virology, immunology and epidemiology of the most common viral causes of acute gastroenteritis (rotaviruses, human caliciviruses, astroviruses, enteric adenoviruses). Clinical symptoms range from mild diarrhoea to life-threatening dehydration, and rotavirus disease is a major cause of childhood mortality, mainly in developing countries. The diagnosis, treatment and preventive measures are reviewed. Uncommon viral causes of acute gastroenteritis and viruses causing gastroenteritis in immunodeficient patients are also discussed. Two live attenuated rotavirus vaccines (Rotarix(RTM), RotaTeq(RTM)) have been licensed in >100 countries since 2006 and used in universal mass vaccination (UMV) programmes. In addition, a new rotavirus vaccine was licensed in India in 2015 for UMV. Although rotavirus vaccines are highly effective in industrialized countries, they are less so in low-income countries of sub-Saharan Africa and South-East Asia. Vaccines against human norovirus disease are under development. Major progress has recently been made in basic research on rotaviruses and human caliciviruses.